2006
DOI: 10.1103/physrevb.73.205120
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures ofLiFePO4andFePO4studied using resonant inelastic x-ray scattering

Abstract: We have studied LiFePO 4 and its delithiated counterpart FePO 4 using the resonant inelastic x-ray scattering ͑RIXS͒ and x-ray absorption techniques. Using Voigt peak fitting, we have found all unresolved RIXS transitions. These energy-loss features were then ascribed to band-to-band transitions by comparison to theoretical density of states ͑DOS͒ calculations. We have found that the DOSs of LiFePO 4 and FePO 4 , as probed with the RIXS technique, agree very well with a theoretical description of the system th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Therefore, the behavior of f 1 is very similar in Fe 1.087 Te and in pure iron. This result confirms that the x-ray absorption for materials related to iron pnictides is qualitatively similar to Fe metal [37] but also very different from Fe ions in the Li x FePO 4 compound for the Li-battery cathodes [38], where multiplet calculations must be included [39]. In the bottom frame of Fig.…”
Section: Resultssupporting
confidence: 77%
“…Therefore, the behavior of f 1 is very similar in Fe 1.087 Te and in pure iron. This result confirms that the x-ray absorption for materials related to iron pnictides is qualitatively similar to Fe metal [37] but also very different from Fe ions in the Li x FePO 4 compound for the Li-battery cathodes [38], where multiplet calculations must be included [39]. In the bottom frame of Fig.…”
Section: Resultssupporting
confidence: 77%
“…Consistent with previous reports, a change in the Fe oxidation state (from 2+ to 3+) upon de-lithiation shifts the main absorption feature in the Fe L 3 edge from ~ 708 to ~ 710 eV. [96][97][98][99][100] Other previously reported spectral features were also satisfactorily reproduced. Excellent fits were obtained at all spatial positions, with a maximum residual of 0.8 % (averaged over all photon energies).…”
Section: Experimental Methodssupporting
confidence: 77%
“…Besides the main components of battery electrode and electrolyte, a stringent requirement of a stable, electron‐insulating, but ion‐conductive (SEI) layer on the surface of corresponding electrodes is necessary to warrant a functional battery cell . Synchrotron based XAS, XES and RIXS have contributed to the understanding of various battery compounds, especially SEI and electrodes . Recently, Achkar et al reported bulk sensitive XAS through inverse partial fluorescence yield measurements, which has been quickly applied to study battery materials …”
Section: Soft X‐ray Absorption Non‐resonant and Resonant Emission Spmentioning
confidence: 99%